2021
DOI: 10.3390/su13158569
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Distinguishing Meaningful Artisan Food Experiences

Abstract: We examine consumer expectations about how specialty versus conventional food products affect well-being and how small, artisan producers can use that information to design better customer experiences. Drawing on recent work examining the costs and benefits of pleasure- and meaning-based consumption, we investigate whether consumer expectations that specialty products are more meaningful lead to increased desire for additional product information. We selectively sampled from the target market of interest: high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Meaningful tourism experiences lead to higher place attachment (W. Lee & Jeong, 2021; Vada et al, 2019a), although the impact on revisit intentions (Rejikumar et al, 2021; Vada et al, 2019b) and word‐of‐mouth is less conclusive (Vada et al, 2019b). Experiencing meaning has also been associated with positive marketing variables such as favourable product evaluations (A. Kim & Briley, 2020; Z. Zhou et al, 2021), favourable attitude towards advertisements and brands (C. Chang, 2020), higher purchase intentions (Xia et al, 2021), seeking product information (Carter & Welcomer, 2021), creating memorable experiences (Sthapit & Coudounaris, 2018; Vada et al, 2019b; Weingarten & Goodman, 2021) and resistance to post‐purchase comparisons (W. Yang et al, 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meaningful tourism experiences lead to higher place attachment (W. Lee & Jeong, 2021; Vada et al, 2019a), although the impact on revisit intentions (Rejikumar et al, 2021; Vada et al, 2019b) and word‐of‐mouth is less conclusive (Vada et al, 2019b). Experiencing meaning has also been associated with positive marketing variables such as favourable product evaluations (A. Kim & Briley, 2020; Z. Zhou et al, 2021), favourable attitude towards advertisements and brands (C. Chang, 2020), higher purchase intentions (Xia et al, 2021), seeking product information (Carter & Welcomer, 2021), creating memorable experiences (Sthapit & Coudounaris, 2018; Vada et al, 2019b; Weingarten & Goodman, 2021) and resistance to post‐purchase comparisons (W. Yang et al, 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Extant research shows that pleasure and meaning evoke different neurological responses in consumers (Luo et al, 2019), but consumers do not necessarily approach consumption as pleasurable or meaningful. Many papers show that pleasure and meaning coexist in the same consumption context (Carter & Welcomer, 2021; Chen & Li, 2018; Güler & Haseki, 2021; Jian et al, 2019; A. Kim et al, 2021; W. Lee & Jeong, 2020; Mugel et al, 2019; Ott et al, 2021; Rieger et al, 2014; Roth et al, 2014; Shaw & Thomson, 2013; Vada et al, 2019b; von Wallpach et al, 2020; Wirth et al, 2012; Zarantonello et al, 2021; H. Zhang et al, 2021). Meaningfulness can also lead to hedonia (C. Chang, 2020; Sthapit & Coudounaris, 2018).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expectations on specialty foods vs. conventional food products that can affect the overall well-being of consumers, and how small-scale artisan producers use this information towards designing better customer experiences are reported by Percival Carter and Welcomer [14]. The study revealed causal mediation analysis in expectations to mediate the link between product types and the utility of product information.…”
mentioning
confidence: 97%